Clinical evaluation for morbidity associated with soil-transmitted helminth infection in school-age children on Pemba Island, Tanzania - Bogoch, Isaac I.; Speich, Benjamin; Lo, Nathan C.; Moser, Wendelin; Croll, David; Ali, Said M.; Ame, Shaali M.; Utzinger, Jürg; Andrews, Jason R.; Keiser, Jennifer (PLOS Neglected Tropical Diseases, 2019)
Background More than 1.5 billion people are infected with soil-transmitted helminths (Ascaris lumbricoides, hookworm, Strongyloides stercoralis, and Trichuris trichiura), causing an estimated global burden in excess of 3 million disability-adjusted life years. However, the relationship between soil-transmitted helminth infection, adverse health consequences, and beneficial effects of deworming are not well understood. Methodology We pursued a detailed longitudinal clinical evaluation of school-age children to evaluate morbidity associated with soil-transmitted helminth infection and responses to treatment. This exploratory study was embedded into a randomized controlled trial. Overall, 434 children, aged 7–14 years, underwent a detailed medical history, physical examination, stool microscopy for soil-transmitted helminths, and hemoglobin (Hb) measurement at baseline. Medical history and stool examination were repeated at 3 and 18 weeks posttreatment. Additionally, Hb measurement was performed at the 18-week treatment follow-up. Logistic regression was employed to assess clinical factors associated with soil-transmitted helminth infection at baseline, and longitudinal data analysis to examine change in health outcomes following treatment over time. Principal findings All enrolled children were infected with T. trichiura, and randomized into four different treatment interventions. None of the medical history, physical examination, and laboratory (i.e., Hb) findings were associated with A. lumbricoides, hookworm, or S. stercoralis infection at baseline. A composite of physical exam findings for anemia, including pallor of the conjunctiva, nail beds, and palmar creases predicted lower Hb values (-3.8 g/dl, 95% confidence interval (CI): -6.9, -0.6 g/dl). When examining longitudinal trends, we did not find improvements to Hb or face Wong-Baker Likert scale among children with soil-transmitted helminth infection compared to those without infection, although there was a slight trend toward improving Hb values after treating hookworm infection. Conclusions/significance Our study demonstrates the challenges of measuring morbidity in the context of soil-transmitted helminth infection and treatment, thus confirming the mainly subtle morbidity effects of infection.